Disaster capitalism : making a killing out of catastrophe - Loewenstein, Antony (Verso Books, 2015)
"Crisis? What crisis? How powerful corporations make a killing out of disaster Award-winning journalist Antony Loewenstein travels across the US, Britain, Afghanistan, Pakistan, Haiti, Papua New Guinea and Australia to witness the reality of Disaster Capitalism--the hidden world of privatized detention centers and militarized private security, formed to protect corporations as they profit from war zones. He visits Britain's immigration detention centers, tours the prison system in the United States, and digs into the underbelly of the companies making a fortune from them. Loewenstein reveals the dark history of how large multinational corporations have become more powerful than governments, supported by media and political elites"--